Water pollution XI - Brebbia, C. A. (WIT transactions on ecology and the environment, 2011)
Water pollution is by necessity an interdisciplinary field involving scientists and professionals with a wide range of expertise. It also transcends national borders, since the contamination of water resources is a problem of global concern.